2016
DOI: 10.1002/ejlt.201600023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoking with smoke flavorings on the oxidative stability of farmed sea bass fillets monitored by 1H NMR and FTIR

Abstract: Farmed European sea bass (Dicentrarchus labrax) fillets were smoked with three commercial smoke flavorings. Unsmoked and smoked fillets were submitted to oxidative conditions to study their oxidative stability. To this aim, at regular intervals of time under oxidative conditions, their lipids were extracted and studied by Fourier transform mid‐infrared spectroscopy (FTIR) and Proton nuclear magnetic resonance (1H NMR). Both kinds of spectra provide markers referred to the beginning and extension of the lipid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Lipid oxidation is one of the main degradative processes occurring in foods in general and in oil and fats in particular, with serious repercussions for food shelf-life, nutrition, and health. Oils in food processing are submitted to very varied conditions, in both industrial and culinary processes, during which their main and minor components might be degraded [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Likewise, some studies have also suggested that during gastrointestinal digestion, oxidation reactions take place, in which lipidic components undergo degradation [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid oxidation is one of the main degradative processes occurring in foods in general and in oil and fats in particular, with serious repercussions for food shelf-life, nutrition, and health. Oils in food processing are submitted to very varied conditions, in both industrial and culinary processes, during which their main and minor components might be degraded [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Likewise, some studies have also suggested that during gastrointestinal digestion, oxidation reactions take place, in which lipidic components undergo degradation [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%